Daily life in Nazi-occupied Europe - Goldberg, Harold J. (Greenwood Press "Daily life through history" series., 2019)
"Daily Life in Nazi-Occupied Europe provides readers with information about political and military affairs, economic life, religious life, intellectual life, and other aspects of daily life in those countries occupied by Nazi Germany during World War II"--